التفاعل بين استراتيجيتي التعلم التنافسي ونمطي وجهة الضبط في بيئة تعلم إلكترونية قائمة على المشروعات وأثره على جودة إنتاج المصادر الرقمية لدى طلاب تكنولوجيا التعليم - خليفة، علي عبدالرحمن محمد; زغلول، إيمان حسن حسن (جامعة الأزهر - كلية التربية, 2019)
This study aims at determining the effect of the interaction between competitive learning strategies and the style of Control point in a project-based e-learning environment on the quality of digital source production among students of educational technology. The researchers used the semi-experimental methodology. Two research tools were used: the control point scale and the digital source quality assessment card. the results indicated that: There is a statistically significant difference between the experimental groups due to the impact of the different competitive learning strategies and the difference in the Control point for the students. There was a correlation between individual competitive learning and internal control and a combination of collective competitive learning and external control. There are also statistically significant differences between the average scores of the digital source quality card for the four experimental groups due to the effect of the interaction between Datasheets and Strategies Competitive Learning and the style of Control point
يهدف هذا البحث إلى تحديد أثر التفاعل بين استراتيجيات التعلم التنافسي ونمطي وجهة الضبط في بيئة تعلم إلكترونية قائمة على المشروعات على جودة إنتاج المصدر الرقمي لدى طلاب تكنولوجيا التعليم. واستخدم الباحثان المنهج شبه التجريبي وتم استخدام أداتين للبحث هما: مقياس وجهة الضبط، وبطاقة تقييم جودة المصدر الرقمي، وأشارت النتائج إلى أنه: يوجد فرق ذو دلالة إحصائية بين المجموعات التجريبية ترجع لأثر اختلاف استراتيجيات التعلم التنافسي واختلاف نمط وجهة الضبط للطلاب حيث ظهر اقتران بين التعلم التنافسي الفردي ووجهة الضبط الداخلية واقتران بين التعلم التنافسي الجماعي ووجهة الضبط الخارجية، كما توجد فروق دالة إحصائيا بين متوسطات درجات بطاقة جودة المصدر الرقمي للمجموعات التجريبية الأربع ترجع لأثر التفاعل بين نمط وجهة الضبط واستراتيجية التعلم التنافسي
Keywords: السياسة التعليمية -- تكنولوجيا التعليم -- التعليم الجامعي -- طلبة الجامعات -- الإستراتيجية التعليمية -- التعلم التنافسي